First record of the plant bug genus Punctifulvius Schmitz from the Oriental Region, with descriptions of three new species (Hemiptera, Heteroptera, Miridae, Cylapinae) - Yasunaga, Tomohide; Wolski, Andrzej; Taszakowski, Artur (Zootaxa, 2023)
Three new species of the fungal-inhabiting plant bug genus Punctifulvius Schmitz, 1978 (Cylapinae: Fulviini) are described, namely P. aleksanderi n. sp. from Selangor, Malaysia, P. parvus n. sp. from East Kalimantan, Indonesia, and P. sakaerat n. sp. from Nakhon Ratchasima, Thailand. The present discovery represents the first record of the genus from the Oriental Region. Punctifulvius members are now confirmed to be widespread from the cold temperate climatic zones in the eastern Palearctic regions, across the tropics of the Oriental Region, to the temperate rainforest of Australia. Punctifulvius kerzhneri Schmitz, 1978 is recorded from Taiwan for the first time. The systematic position of Teratofulvioides Carvalho & Lorenzato, 1978 is discussed, and its single species Teratofulvioides punctatus Carvalho & Lorenzato, 1978 is redescribed. Color adult habitus images of Punctifulvius aleksanderi, P. kerzhneri, P. parvus, P. sakaerat, and Teratofulvius punctatus, images of male (P. parvus and P. sakaerat) and female (P. aleksanderi) genitalic structures, as well as scanning electron micrographs of selected structures of P. aleksanderi, P. kerzhneri, P. parvus, P. sakaerat, and T. punctatus are provided. Key to the species of Punctifulvius is given.